Factors affecting the adoption of e-learning: a study among postgraduate students in sri lanka - Kaveesha, S.; Kumara, P.D.K.A.; Samarasinghe, S.M. (University of Jaffna, 2019)
The growth of technology has created a necessity to move from conventional means of education to modern educational means. This is where e-Learning comes into consideration. Further, with the recommendation of the Quality Assurance and Accreditation Council of the University Grants Commission in Sri Lanka, it is vital to incorporate e-Learning into the higher education system and thus, universities have adopted e-Learning into the learning process. However, in particular, postgraduate students in particular, are reluctant to use e-Learning for their education and have little insights on the adoption process of e-Learning in postgraduate studies. Therefore, the objectives of this research were to identify the factors affecting the adoption of e-Learning and to explain the adoption process of e-Learning in thepostgraduate education sector in Sri Lanka. The conceptual model was developed based on the Unified Theory of Acceptance and Use of Technology (UTAUT) model which includes Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Intention to use of e-Learning and the use of e-Learning.The model was empirically tested through survey data collected from university postgraduate students. The structural equation modeling (SEM) technique was used with the Smart PLS program to test the conceptual model. The results confirmed UTAUT as a good theoretical model to explain the adoption process of e-Learning. Further, it is hoped that the resultswill help to promote the successful integration of e-Learning in teaching and learning process in postgraduate education.
Keywords: e -learning; e-learning adoption; UTAUT model